Perancangan Sistem Layanan Informasi Akademik Berbasis Web pada Fakultas Teknik Universitas Bhayangkara Jakarta Raya - Dwi Swasono Rachmad (Universitas Indraprasta PGRI Jakarta, 2019)
Academic Information Services at a Faculty is very important to provide and provide information needed by students. But this is not the case, because the faculty of engineering still does not provide services in providing accurate information due to the absence of an information system that facilitates all the requirements for services to students. Therefore, the need for designing this information system is expected to be a tool for the faculty in providing information and also makes it easier for students to get access to information anywhere and anytime without coming to campus to find out the latest information. With a web-based application that can be accessed by mobile devices and others, the information that will be obtained for students can be received quickly, precisely and accurately because the management of the information system is managed directly by the faculty. Thus, students get information on the Faculty of Engineering's academic information services without having to first come to campus, by using a web-based application as an information system that is easily accessed